A pesquisa como ferramenta de ensino em sociologia: sentidos, obstáculos e potencialidades em livros didáticos e em práticas docentes - David Gonçalves Soares (Universidade do Vale do Rio dos Sinos (UNISINOS), 2017)
This article presents an introductory reflection on the use of research as a teaching tool of Sociology. This premise can be found in normative documents such as the Curricular Guidelines for High School, and also in the National Common Curricular Basis. Its goal is to reflect upon the possibilities of use of this tool, which has been shown as an ideal to be pursued in the field of sociology teaching. From the exposure of the senses associated with it, the work analyzes the research proposals of two textbooks, as well as interpreting the interviews of teachers from a school considered excellent (CAp-UERJ). Among the results, the following can be highlighted: the difference between the most informative and the most systematic and methodological types of research, the apparent consensus regarding the importance of research in teaching sociology, and the polysemy in which the teachers identify the word “research”. Furthermore, structural obstacles were identified for the routine didactic use of sociological research, such as: the short time allocated for the subject in the curriculum; the absence of a school climate that stimulates and develops mechanisms to facilitate pedagogical innovation; deficient teacher training, which does not emphasize research as a teaching principle; and the need for a quantum of cultural capital from students to a profitable use of this teaching tool.